Exploring The Role of Halal Certification for Tourism Industry in Aceh - Zulhilmi, Zulhilmi; Terpiadi, Sariyulis; Hafizh, Muhammad (el-Amwal, 2024)
The growing demand for halal goods and services from both domestic and international customers has prompted Aceh's hotels and other service providers to plan their marketing strategies to penetrate the halal market. In Aceh, hoteliers have responded to the growing demand for halal goods and services by offering Shariah Compliant Hotel to satisfy the needs of Muslim travellers. This study aims at investigating the perception of halal certification among tourism stakeholders in Aceh towards the implementation of Shariah compliant hotel. This study applied the diffusion of innovation theory as a guidance and used the qualitative approach through in-depth interview of tourism stakeholders. The study revealed that halal certification is essential as a standard for Aceh as a Shariah province and that halal tourism is an innovative concept to preserve Islamic teaching in the tourism business. Academically, this study adds to the existing literatures on service innovation and Shariah Compliant Hotel